A pilot single-centre randomized trial assessing the safety and efficacy of lateral pararectus abdominis compared with transrectus abdominis muscle stoma placement in patients with temporary loop ileostomies: the PATRASTOM trial - Hardt, Julia; Seyfried, Steffen; Weiß, Christel; Post, Stefan; Kienle, Peter; Herrle, Florian (Colorectal disease, 2016)
Aim Transrectal stoma placement is considered the standard technique for positioning a stoma. A prospective series using a novel method of lateral pararectal stoma placement recently revealed a remarkably low stoma herniation rate. A randomized trial was conducted to compare the lateral pararectal with the transrectal stoma position with regard to parastomal herniation, stoma-related morbidity and quality of life. Method Adult patients undergoing elective placement of a temporary loop ileostomy were eligible for inclusion. Patients were intra-operatively randomized to undergo either a lateral pararectal or a transrectal ileostomy. The primary end-point was the rate of parastomal herniation. Secondary end-points included other stoma-related complications and quality of life. Sample size calculation resulted in 54 patients having to be analysed to detect a difference of parastomal herniation of 30% with an 80% power and a 5% significance level. The trial was registered with the German Clinical Trials Register (registration number DRKS00003534). Results Between April 2012 and April 2014, 30 patients were randomized to each group. The incidence of parastomal herniation did not differ between the lateral pararectal (5 of 27) and the transrectal group (4 of 29; P = 0.725). There was also no significant difference regarding other stoma-related complications and the EORTC quality of life scales C30 and CR29. Conclusion The incidence of parastomal herniation and other stoma-related complications did not differ between the groups. However, due to the limited sample size a small difference in favour of one of the two stoma placement techniques cannot be entirely ruled out.